FORMING APPROPRIATE CONCEPTUAL FRAMEWORKS: TOWARDS A FRAMEWORK FOR THE STUDY OF LITERARY RESPONSE IN L2 - Kamsilawati Kamlun; Chelster Sherralyn Jeoffrey Pudin; Eugenia Ida Edward; Irma Wani Othman, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
The aim of this study is to look into the notion of literary reading and response in L2 by pre-service teachers in Malaysia in order to improve teacher education. The researchers will provide an outline of Reader Response theories and how they affect the learning of literature in L2 in this study. The researchers will go over their conceptual framework, which was developed based on past research. This conceptual framework will be developed in order to conduct in-depth research on pre-service teachers' perceptions of literary reading in L2 and to assist them in improving their practises in the classroom. Using the conceptual framework, based on Reader Response Theory, it allows researchers to explore what types of responses pre-service teachers have to literary texts while they are involved in the reading process. Hoping that the experience will aid in the improvement of teaching and learning.